Extremely long cupulae of embryonic neuromasts in cyprinid fish - Mukai, Yukinori; Kobayashi, Hiroshi (1993)
Willow shiner delayed hatching embryo had extremely long cupulae. The length was about 500 μm. Especially delayed hatching embryo had longer cupulae.